Perilaku Wakaf Elit Agama Kota Malang: (Studi Konstruk Elit Agama Kota Malang Terhadap Wakaf Uang) - Fakhruddin; Dwi Hidayatul Firdaus (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2020)
Waqf is also an instrument for creating justice and prosperity in the economic field. The main characteristic of endowments is when endowments have been fulfilled, then there is a shift in ownership from the owner to the ownership of Muslim communities which are expected to last and provide sustainable benefits. Waqf in the form of money (endowments of money) is seen as one way to make endowments can provide better and more results. Researchers are interested in conducting research on this waqf with a focus on looking at the behavior of the religious elites of the city of Malang in understanding and actualizing the endowments of money in their lives. In this case the religious elite of the city of Malang took samples from the Nahdlotul Ulama Organization (NU), Muhammadiyah and the Indonesian Islamic Da'wah Institute and some of the City boarding school caretakers. With the formulation of the problem 1) What are Malang City's religious elite views on the concept and implementation of cash waqf? 2) What is the appropriate format according to the religious elite of Malang City on the application of cash waqf? The type of research that will be used in this research is field research, namely research conducted in the arena or field of symptoms. With this type of research is expected to collect data and information obtained directly from respondents about the endowment of money for the religious elite in the city of Malang. The results of this study are the first religious elites of Malang City in terms of cash waqf giving legal jaiz in other words the practice of waqaf is not only dominated by the object of the object immovable waqaf, because it sees the situation and conditions that exist in society and for general welfare and not conflict with Sharia. Whereas in practice, the religious elite of Malang City has not yet carried out the mandate of the regulation stating that it must be orderly administration in terms of permits to be Nazar, deed of pledge waqaf and in cooperation with Islamic Financial Institutions (LKS). Second, the lack of information and socialization about this cash waqf, then the format that occurs in the community in applying this cash waqf is by directly giving the cash waqf property to Nazir directly. money that was forgiven. So that the religious elites of Malang also practice from what was signed above, because the contract directly from waqif explains in the contract for what the money is. As Muhammadiyah and other religious elites on that day also directly allocate the cash waqf received on the object of the contract that was explained at the time of the Waqf contract.